The Influence of Brand Perception on Purchase Intention from the Perspective of Consumer Culture - Cao, Lei; Albdiwy, Feras Fathi (International Journal of Global Economics and Management, 2025)
Aiming at the influence of consumer culture, this paper explores whether the integration of different elements into Chinese brands has an impact on consumers' global brand perception, perceived functional benefits, perceived symbolic benefits, and purchase intention, as well as the differences in the degree of impact. Based on previous studies, the paper divides the perceived symbolic benefit into three dimensions: brand reputation, unique benefit and global citizenship, and explores the mechanism of the influence of perceived globality on purchase intention. The openness of consumer culture is introduced as a moderating variable to verify whether it has a moderating effect on the overall effect of perceived globality and purchase intention. Most of the research is aimed at local promotion, so that brands can stand in a cultural perspective and infect more global consumers. In this study, the experimental method was adopted to collect data through a questionnaire and a formal experimental questionnaire. After screening, SPSS 21.0 was used for statistical analysis of valid data. The results show that: (1) Compared with local elements, Chinese local brands with global or foreign elements can make consumers perceive more global; Compared with local and foreign elements, local brands with foreign elements are more willing to buy. (2) Brand perceived globality positively influences perceived functional and symbolic benefits, and has a more significant impact on the latter's global citizenship attributes. (3) Consumer cultural openness positively moderates the impact of perceived globality on perceived functional and symbolic benefits. According to the conclusion of the research, the author provides corresponding suggestions for Chinese brands to carry out marketing in domestic and overseas markets. Finally, the limitations and future prospects of this study are pointed out.